CHARACTERIZATION OF MELOXICAM AND MALONIC ACID COCRYSTAL PREPARED WITH SLURRY METHOD - Najih, Yuli Ainun; Widjaja, Bambang; Riwanti, Pramudita; Mu'alim, Ade Ianaini (Journal of Islamic Pharmacy, 2018)
Meloxicam (MLX) is a nonsteroidal anti-inflammatory drugs (NSAID) which belong to Biopharmaceutical Classification System (BCS) class II, which have a low solubility level with a high permeability. Therefore, to enchance is solubility level, physical modification of the meloxicam is required. It  can be done by the cocrystal formation. Cocrystal contained active ingredients and coformer which bind through the hydrogen bond. This study used malonic acid (MA), since it contained carboxylic group which expected to form hydrogen bonds. Slurry is a method of cocrystal formation by mixing two ingredients, i.e. active ingredients of the drugs and its cofomer, dissolved in a solvent and may be formed due to the heat energy released by the friction between particles and their crusher. This study aimed to determine the characteristic of meloxicam-malonid acid cocrystal by 1:1 mol ratio using PXRD, DSC and FTIR. The result of PXRD charaterization indicated a new peak at angle 9,4° and 18,5°. The result of DSC characterization indicated an endothermic peak with a low melting point at 97,64°C ; 152,62°C ; 176,87°C temperature. The result of FTIR characterization indicated a shirt of the O-H uptake band from at wave number 3126-2980 cm-1 to 3292-2951 cm-1, the N-H uptake band of meloxicam at wave number 3492 cm-1 to 3525 cm-1